The Influence of Utilization of Sweet Potato Leaves (Ipomoea batatas) as an Eating Feed to Increase the Body Weight on Goat Crossbreed of Ettawa - K. Kamari (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2018)
Sweet potato leaf (Ipomoea Batatas) is a potential agricultural waste is used as animal feed to Goat crossbreed of Ettawa. Sweet potato leaf (Ipomoea Batatas) has a high enough protein content (> 20%), so it can be used as a source of protein goat crossbreed of Ettawa. This research aims to determine the effect of feeding of sweet potato leaves (Ipomoea Batatas) as feed on goat body weight of goat crossbreed of Ettawa. This research has been conducted in February to March 2015, located in Wonua Raya village, Toari district, Kolaka Regency. This research uses 12 goats crossbreed of Ettawa which is divided into 12 plots of cages. In this research, four levels of feeding treatment were applied: regular feed/Gamal leaf (R0), 90% Gamal leaves + 10% sweet potato leaves (R1), 85% Gamal leaves + 15% sweet potato leaves (R2), 80 % Leaf Gamal + 20% sweet potato leaves (R3). The results showed that the use of sweet potato leaves on weighing 15 days did not significantly affect the rate of body weight and had a significant effect on considering at day 30 (p